Fungi and Archaea Control Soil N2O Production Potential in Chinese Grasslands Rather Than Bacteria - Zhong, Lei; Qing, Jinwu; Liu, Min; Cai, Xiaoxian; Li, Gaoyuan; Li, Frank yonghong; Chen, Guanyi; Xu, Xingliang; Xue, Kai; Wang, Yanfen (Frontiers in Microbiology, 2022)
Nitrous oxide (N2O) is a powerful greenhouse gas and the predominant stratospheric ozone-depleting substance. Soil is a major source of N2O but remains largely uncertain due to the complicated processes of nitrification and denitrification performed by various groups of microbes such as bacteria, fungi, and archaea. We used incubation experiments to measure the total fungal, archaeal, and bacterial N2O production potential, and the microbial functional genes in soils along a 3000 km Chinese grassland transect, including meadow steppe, typical steppe, desert steppe, alpine meadow, and alpine steppe. The results indicated that fungi, archaea, and bacteria contributed 25%, 34%, and 19% to nitrification and 46%, 29%, and 15% to denitrification. The AOA, AOB genes were notably correlated with the total nitrification enzyme activity (TNEA), whereas both narG and nirK genes were significantly correlated with total denitrification enzyme activity (TDEA) at p < 0.01. The correlations between AOA and ANEA (archaeal nitrification enzyme activity), AOB and BNEA (bacterial nitrification enzyme activity), as well as narG, nirK, and BDEA (bacterial denitrification enzyme activity) showed higher coefficients than those between the functional genes and TNEA/TDEA. The structural equation modeling (SEM) results showed that fungi are dominant in N2O production processes followed by archaea in Northern Chinese grasslands. Our findings indicate that the microbial functional genes are powerful predictors of the N2O production potential, after distinguishing bacterial, fungal, and archaeal processes. The key variables of N2O production and the nitrogen (N) cycle depend on the dominant microbial functional groups in the N-cycle in soils.